Effectiveness of Objective Structured Clinical Examination Training Related to Attitude and Satisfaction Level among Nursing Faculty Members: OSCE Training Related to Attitude and Satisfaction Level - Haq, Fazal; Bashir, Shahzad; Kumar, Santosh (NURSEARCHER (Journal of Nursing & Midwifery Sciences), 2026)
The Objective Structured Clinical Examination (OSCE) is a standardized method used to objectively assess nurses’ clinical competencies through simulated stations that evaluate skills such as communication, history-taking, physical examination, and clinical procedures. Objectives: To determine the effects of OSCE training related to attitude and satisfaction level among nursing faculty members. Methods: The study design was a pre- and post-quasi-experimental study without a control group. 56 participants were recruited through a purposive sampling technique from six private nursing institutes over three months, from June to August 2023. Attitude level was measured on a valid and reliable Likert scale consisting of 18 questions, and satisfaction level was measured on a valid and reliable Likert scale consisting of 30 questions. Data were analyzed through SPSS version 24.0. Paired t-test was applied to compare pre- and post-mean differences, chi-square test for assessing the association among demographic variables, and ANOVA was utilized to compare the institutes. Results: Out of the 56 participants, 36 were male, and 20 were female. After the intervention, significant mean differences were seen in both attitude and satisfaction levels, with a mean difference of 46.45 ± 6.798 to 80 ± 6.048 for the attitude level at (p<0.001) and 78.88 ± 10.364 to 134.43 ± 11.483 for the satisfaction level at (p<0.001). Conclusions: The effectiveness of OSCE training is found to be significant among faculty members related to attitude and satisfaction level.